2004
DOI: 10.1007/s00222-004-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Simply connected symplectic 4-manifolds with b2+=1 and c12=2

Abstract: Abstract. In this article we construct a new family of simply connected symplectic 4-manifolds with b + 2 = 1 and c 2 1 = 2 which are not diffeomorphic to rational surfaces by using rational blow-down technique. As a corollary, we conclude that a rational surface CP 2 ♯7CP 2 admits an exotic smooth structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 16 publications
0
80
0
Order By: Relevance
“…(e.g. [1,3,7,16,21,22,25,24,26,27,31,41,42,53].) Resting on spectacular results of Taubes on Seiberg-Witten invariants of symplectic 4-manifolds, these constructions have demonstrated that minimal symplectic 4-manifolds not only constitute small exotic 4-manifolds (which are homeomorphic but not diffeomorphic to standard ones), but also resource them in almost all the known instances.…”
Section: Introductionmentioning
confidence: 98%
“…(e.g. [1,3,7,16,21,22,25,24,26,27,31,41,42,53].) Resting on spectacular results of Taubes on Seiberg-Witten invariants of symplectic 4-manifolds, these constructions have demonstrated that minimal symplectic 4-manifolds not only constitute small exotic 4-manifolds (which are homeomorphic but not diffeomorphic to standard ones), but also resource them in almost all the known instances.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, new methods were developed [Pa05,ABP07] to construct symplectic 4-manifolds with small topology and exotic smooth structures. Moreover, the method proposed by J.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the method proposed by J. Park [Pa05] was later refined [LePa07,PPS07] to produce interesting examples of minimal complex surfaces of general type. In this paper we show how we can use these constructions in regard to the existence or non-existence of Einstein metrics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations